Hyperbaric oxygen therapy in peroneal nerve damage due to lithotomy position - Akan, Serkan; Ediz, Caner; Cihan Temel, Muhammed; Yilmaz, Omer (Annals of Medical Research, 2021)
None
Keywords: Hyperbaric oxygen; peroneal nerve; urethroplasty; lithotomy position.